Palliative care need in the Eastern Mediterranean Region and human resource requirements for effective response. - Eric L Krakauer; Xiaoxiao J Kwete; Maryam Rassouli; Héctor Arreola-Ornelas; Hadis Ashrafizadeh; Afsan Bhadelia; Yuwei A Liu; Oscar Méndez-Carniado; Hibah Osman; Felicia M Knaul (Public Library of Science (PLoS), 2023)
Integration of palliative care into health care systems is considered an ethical responsibility, yet no country in the Eastern Mediterranean Region (EaMReg) has achieved integration. Data on palliative care need and cost are crucial forEaMReg health care planners and implementers in the region. Using data from the Lancet Commission on Palliative Care and Pain Relief, we estimated the number of people in each EaMReg country who needed palliative care in 2015 and their degree of access. In three countries, we estimated the number of days during which an encounter for palliative care was needed at each level of the health care system. This enabled calculation of the number of full-time equivalents (FTEs) of clinical and non-clinical staff members needed at each level to administer the essential package of palliative care recommended by WHO. In 2015, 3.2 million people in the EaMReg needed palliative care, yet most lacked access to it. The most common types of suffering were pain, fatigue, weakness, anxiety or worry, and depressed mood. To provide safe, effective palliative care at all levels of health care systems, between 5.4 and 11.1 FTEs of trained and supervised community health workers per 100,000 population would be needed in addition to 1.0-1.9 FTEs of doctors, 2.2-4.3 FTEs of nurses, and 1.4-2.9 FTEs of social workers. Data from our study enables design of palliative care services to meet the specific needs of each EaMReg country and to calculate the cost or cost savings.